PENGARUH SUPERVISI KLINIS DAN EFIKASI DIRI TERHADAP KOMPETENSI PEDAGOGIK GURU DI SMKN KOTA ADMINISTRASI JAKARTA BARAT - Emilia Sari (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2020)
The purpose of this study is to determine whether there is a positive direct effect of clinical supervision and self-efficacy on teacher pedagogical competence. A total of 72 teachers are used as research samples to obtain data which will be analyzed by quantitative methods of path analysis. The results showed that there was a positive direct effect (1) clinical supervision on teacher pedagogical competence. (2) self-efficacy of the teacher's pedagogical competence. (3) clinical supervision of self-efficacy.